ChemInform Abstract: Salen Complex of Cu(II) Supported on Superparamagnetic Fe3O4@SiO2 Nanoparticles: An Efficient and Recyclable Catalyst for Synthesis of 1‐ and 5‐Substituted 1H‐Tetrazoles. Issue 3 (21st January 2014) - Dehghani, Farzaneh; Sardarian, Ali Reza; Esmaeilpour, Mohsen
Abstract An efficient and general method for the synthesis of 1‐ and 5‐substituted 1H‐tetrazoles using a salen Cu(II) complex supported on magnetite‐silica nanoparticles as the catalyst is reported.